2018
DOI: 10.23880/whsj-16000106
|View full text |Cite
|
Sign up to set email alerts
|

“Oral Menopause” - Do you know this Phenomenon?

Abstract: Patients as well as therapists, even dental professionals, are not fully aware of the fact that menopausal oral problems can seriously impair quality of life. However, hormone receptors in the oral mucosa may cause dry mouth and mucous membrane pain due to menopausal hormone changes. Some disease entities such xerostomia, oral lichen planus, or "Burning Mouth Syndrome" are significantly more common during and after menopause and present problems for patients and therapists alike. Increased knowledge, awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The patients usually report a reduction in salivary flow, even though the fact that in only onethird of all cases hyposialia is present. [471314] A destructive correlation was witnessed among the severity of dry mouth sensation and the salivary concentration of 17beta-estradiol in a case–control study conducted on 38 postmenopausal women. Adequate water consumption must be advised for these patients, along with sugar-free candies or munching gum to encourage salivation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients usually report a reduction in salivary flow, even though the fact that in only onethird of all cases hyposialia is present. [471314] A destructive correlation was witnessed among the severity of dry mouth sensation and the salivary concentration of 17beta-estradiol in a case–control study conducted on 38 postmenopausal women. Adequate water consumption must be advised for these patients, along with sugar-free candies or munching gum to encourage salivation.…”
Section: Discussionmentioning
confidence: 99%
“…Menopause is a physiological event for women caused by failure of ovarian follicular function that leads to decreased secretion of ovarian hormones estrogen and progesterone. [ 3 , 4 ] Women’s bodies go through biological and endocrine changes during the menopause that have impact on their health, particularly on the generation of sex hormones. The oral cavity is immediately impacted by changes in hormone levels because the oral mucosa includes estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a higher incidence of OLP in perimenopausal compared with premenopausal women (10.9% compared with 0.5–2%) 4 . Patients with the ulcerated, erosive or bullous form of lichen planus have a significantly reduced quality of life due to pain 19 …”
Section: Immune‐mediated Conditionsmentioning
confidence: 99%
“…4 Patients with the ulcerated, erosive or bullous form of lichen planus have a significantly reduced quality of life due to pain. 19 Management of OLP includes a variety of topical, systemic and nonpharmacological preparations, listed in Table 2. A systematic review conducted by Oberti et al 20 found the most effective first-line treatment for OLP was topical corticosteroids, while for management of refractory cases, topical calcineurin inhibitors were effective as second-line treatment.…”
Section: Oral Lichen Planusmentioning
confidence: 99%
See 1 more Smart Citation